Clinical study of AIDS complicated with fungal infection - Gao, Zihao (International Journal of Public Health and Medical Research, 2024)
This paper presents a systematic study on the common occurrence of concurrent fungal infections in AIDS patients in clinical practice. Firstly, it introduces the epidemiological status of AIDS worldwide, emphasizing the special vulnerability to fungal infections due to the impaired immune function of AIDS patients. Subsequently, it analyzes in detail the incidence, clinical features, and diagnostic methods of common fungal infections in AIDS patients. Furthermore, it discusses the impact of fungal infections on the disease progression and prognosis of AIDS patients and provides a comprehensive review of prevention and treatment strategies. By summarizing and synthesizing the latest research findings and clinical experiences, this paper emphasizes the importance of timely diagnosis and treatment of fungal infections, and proposes directions for further research and recommendations for future clinical practice.